THE EFFECT OF CHAIN DRILL TECHNIQUE ON STUDENTSâ€™ SPEAKING ACHIEVEMENT AT SMP NEGERI 3 RAHA - SHYERLIN SONI, WA ODE (Universitas Halu Oleo, 2019)
This study aims to find out whether there is a significant effectof chain drill technique on the first year of SMP Negeri 3 Raha. Theresearch question formulated â€œis there any significant effect ofchain drill technique on studentsâ€™ speaking achievement at SMPNegeri 3 Raha?â€. The design of study was pre-experimentalresearch design that consisted of one group pre-test and post-test.The population of this study was all students on the first year ofSMP Negeri 3 Raha who were registered in academic year2017/2018. The sample of this study was one class namely VII3which consisted of 22 students. The instrument of this study wasoral test in dialogue based on the cue card about how to greet andrespond. The research used Paired Sample T- test to analyze theresult of the study of the effect of chain drill technique on studentsâ€™speaking achievement after analyzing the normality of the data inthe experimental class. The result shows that studentsâ€™ speakingability in the post test is 2.806 higher than 1.647 is the post test.The hypothesis testing is found that the level of significant is 0.00,since the level of significance value is less than 0.05, i.e.0.00<0.05, the null hypothesis (H0) is rejected and H1 is accepted.It means that the use of chain drill technique shows a significantdifference on studentsâ€™ speaking achievement on the first year ofSMP Negeri 3 Raha based on the result of the post-test.Keywords: Speaking, Teaching Speaking, Chain Drill Technique